Challenges of smart cities in India - Chitta Pathak (European Regional Science Association (ERSA), 2016)
In 2015, the Central Government of India has added a new dimension to Urbanization and Urban development policy and has introduced the concept of Smart Cities. At the beginning the concept was not elaborated. Does it mean inclusive development of the selected cities? Could they correct the spatial and structural imbalance of urban development in India? The government took almost a year to define such smart cities and has identified about 100 such smart cities for integrated urban development. To start with only twenty such cities would be taken up for planning and development in 2016 Independent India has inherited a spatially and structurally imbalanced urban development dominated by the large cities (metropolises, mega cities, etc) with deficiency of small and medium size towns. To achieve balanced urban development the government introduced the concept of integrated development of small and medium size towns (in 1974) and to re-orient the rural-urban migration away from the large size cities. The policy has continued even now but had limited success in urban development. In 1980s, the Urbanization Commission has (1986) suggested the development of selected urban areas having potential for development but still the large size cities have grown unabatingly and migration towards the metro cities continued. Because of weak economic base the small & medium size towns could not keep pace with the urbanization process. The latest Population Census of India (2011) has analyzed the urbanization pattern in India. It shows that India has achieved the level of urbanization (31.16%) with annual growth rate of 2.76 percent. There are 7,935 urban areas with 377.1 million urban population and 466 cities having population more than hundred thousand (1, 00,000). The urbanization pattern in India has been supported by the development of tertiary sector of the economy rather than backed by commensurate economic growth. In 2011, about ten megacities have dominated the urban structure accounting for more than 20% of urban population while the share of the small & medium size towns remain low. The urban growth has shifted spatially from the metro cities (mega cities) to the peri-urban areas with rapid horizontal expansion of the metropolitan areas (urban fringes). Whether this urbanization trend could be regulated is an open question. The role of smart cities in urban development has been examined in the context of their sustainability, inclusive growth and aspiration of the citizen.
Keywords: 330